Programme coverage, condom use and STI treatment among FSWs in a large-scale HIV prevention programme: results from cross-sectional surveys in 22 districts in southern India. (18th February 2010) - Ramakrishnan, Lakshmi; Gautam, Abhishek; Goswami, Prabuddhagopal; Kallam, Srinivasan; Adhikary, Rajatashuvra; Mainkar, Mandar K; Ramesh, Banadakoppa M; Morineau, Guy; George, Bitra; Paranjape, Ramesh S
Abstract : Objective: This paper evaluates Avahan programme's coverage of female sex workers (FSWs), focus on high-risk FSWs and intermediate outcomes. Methods: First round of cross-sectional survey data, Integrated Behavioral and Biological Assessments (IBBA), conducted in 22 districts, were aggregated into district categories: Solo, where Avahan was the sole service provider covering all FSWs and Major or Minor where Avahan was not the sole provider, but intended coverage was >50% or ≤ 50% of FSWs respectively. Multivariate logistic regression was applied to compare exposure by district categories, vulnerability factors and intermediate outcomes associated with exposure. Results: Reported exposure, evaluated on basis of having received any of three core services, was higher in Solo (75%) compared with Minor (66%) districts. Logistic regression showed that FSWs in solo districts were more likely to be exposed (adjusted odds ratio (AOR)=1.5; 95% CI 1.20 to 1.86) compared with FSWs in Minor districts. Multivariate analysis in Solo districts revealed that FSW with ≥15 clients in the past week had a higher chance of being exposed to core services (AOR=1.56; 95% CI 1.03 to 2.35). Exposure to the three services in Solo Avahan districts was significantly associated with correct knowledge on condom use (AOR=1.36; 95% CI 1.05 to 1.78), consistent condom use with occasional clients (AOR=3.17; 95% CI 2.17 to 4.63) and regular clients (AOR=2.47; 95% CI 1.86 to 3.28) and STI treatment-seeking behaviour (AOR=3.00; 95% CI 1.94 to 4.65). Conclusions: Higher coverage of FSWs was achieved in districts where Avahan was the only intervention compared with districts having multiple and longstanding non-Avahan programmes. Exposure in Solo districts was associated with intermediate outcomes; this need to be further evaluated in comparison with non Avahan areas and substantiated through data from next IBBA.